The vision of James - James, William, 1842-1910 (Spirit of philosophy series, 1996)
William James had the courage to experience the collision of European and American ways of thinking head on, and to emerge from it with a new philosophy - one displaying a remarkable vitality for dealing with the transformative issues at the core of the human condition. This easy to read introduction to his life and work explains why James' work is overwhelmingly valuable to us today in getting to grips with the spiritual dimension of human experience.